31‐2: Invited Paper: Nanostructures Oxide Thin‐Film Transistors Fabricated by Near‐Field Nanolithography with Enhanced Device Performance. Issue 1 (25th September 2020) - Huang, Kairong; Chen, Zihao; Hu, Sujuan; Gao, Lichao; Liu, Chuan
Abstract : We have developed oxide TFTs with nanostructure by using a strategy based on near‐field nanolithography, such as wrapping insulator structure with nano‐splitting active layer or nanoscale and periodic degenerately doped heterostructures. These nanostructured TFTs enhanced in device performance, compared with normal single gate homogeneous IGZO TFTs.